The pre‐gestational triglycerides and high‐density lipoprotein cholesterol ratio is associated with adverse perinatal outcomes: A retrospective cohort analysis. Issue 3 (13th January 2020) - Arbib, Nissim; Pfeffer‐Gik, Tamar; Sneh‐Arbib, Orly; Krispin, Eyal; Rosenblat, Orgad; Hadar, Eran
Abstract: Objective: To investigate associations between pre‐gestational dyslipidemia, expressed as the ratio between triglycerides (TG) and high‐density lipoprotein cholesterol (HDL), and adverse maternal and neonatal outcomes. Methods: A retrospective cohort analysis included women with TG and HDL measurements available up to 52 weeks before conception who delivered a singleton, non‐anomalous infant. The study population was stratified according to a TG/HDL ratio cutoff of 3. Primary maternal outcomes included gestational diabetes or hypertensive disorders of pregnancy and neonatal outcomes after delivery before 37 weeks. Results: Among 5226 women included, 4446 (85.1%) had TG/HDL <3 and 780 (14.9%) ≥3. TG/HDL ratio ≥3 vs <3 was associated with higher rates of gestational diabetes (13.1% vs 5.2%, P <0.0001) and hypertensive disorders of pregnancy (5.3% vs 2.2%, P <0.0001). Larger babies (3229.7 ± 520.7 g vs 3181.7 ± 504.4 g, P =0.015) with higher birth weight percentile (59.0 ± 26.4 vs 55.1 ± 26.6, P <0.0001) and increased rates of large‐for‐gestational‐age (14.5% vs 10.8%, P =0.007) and macrosomia (5.6% vs 3.9%, P =0.026) were found. In multivariate analysis, TG/HDL ≥3 remained an independent risk‐factor for gestational diabetes (adjusted odds ratio [aOR] 1.56, 95% confidence interval [CI] 1.02–2.39) and pre‐eclampsia (aOR 3.02, 95% CI 1.82–5.01). Conclusions: An increase in adverse pregnancy outcomes was reported, mainly gestational diabetes and pre‐eclampsia, when TG/HDL ratio up to 1 year before pregnancy was ≥3. Abstract : Pre‐pregnancy triglyceride and high‐density lipoprotein cholesterol ratio ≥3 up to 1 year before conception is associated with adverse outcomes—mainly gestational diabetes and pre‐eclampsia.